2020
DOI: 10.1186/s12887-020-02326-z
|View full text |Cite
|
Sign up to set email alerts
|

Child acceptability of a novel provitamin A carotenoid, iron and zinc-rich complementary food blend prepared from pumpkin and common bean in Uganda: a randomised control trial

Abstract: Background: Ugandan children are fed homemade complementary foods (CFs) which are usually deficient in vitamin A, iron and zinc. Novel homemade CFs rich in vitamin A, iron and zinc need to be developed, and assessed for their acceptability among target children. Objective: Homemade provitamin A carotenoids (PVACs), iron and zinc-rich complementary food (CF), common bean pumpkin blend (BPB) formulated from pumpkin (Sweet cream) and common bean (Obwelu) and PVAC-rich pumpkin blend (PB) from Sweet cream were prep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Moreover, over 100% PVAC retention was also observed after boiling or steaming provitamin A biofortified pumpkin (Carvalho et al 2015). Studies by Carvalho et al (2014) and Carvalho et al (2015) are consistent with several other studies that showed that PVAC retention was over 100% in pumpkin puree prepared from either boiled or steamed pumpkin (Bulatova et al 2018;Buzigi, Pillay, and Siwela 2020a;Maier et al 2008;Provesi, Dias, and Amante 2011). The higher retention of b-carotene content observed in cooked pumpkin may be due to the cis-b-carotene isomers that increase on heating PVAC rich foods (Azizah et al 2009;Bechoff et al 2017;Bengtsson et al 2008;De Moura, Miloff, and Boy 2015;Mugode et al 2014).…”
Section: Home Cooking Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, over 100% PVAC retention was also observed after boiling or steaming provitamin A biofortified pumpkin (Carvalho et al 2015). Studies by Carvalho et al (2014) and Carvalho et al (2015) are consistent with several other studies that showed that PVAC retention was over 100% in pumpkin puree prepared from either boiled or steamed pumpkin (Bulatova et al 2018;Buzigi, Pillay, and Siwela 2020a;Maier et al 2008;Provesi, Dias, and Amante 2011). The higher retention of b-carotene content observed in cooked pumpkin may be due to the cis-b-carotene isomers that increase on heating PVAC rich foods (Azizah et al 2009;Bechoff et al 2017;Bengtsson et al 2008;De Moura, Miloff, and Boy 2015;Mugode et al 2014).…”
Section: Home Cooking Methodssupporting
confidence: 65%
“…This may indicate that the cereal, "instant dhokla" diluted the b-carotene content in pumpkin powder on mixing pumpkin powder and the cereal to form "instant dhokla-pumpkin powder mix". Such a reduction in PVAC content in pumpkin was also observed by Buzigi, Pillay, and Siwela (2020a), after mixing pumpkin with common bean to form common bean pumpkin blend (BPB). It is likely that common bean diluted the PVAC content of pumpkin on blending pumpkin to form BPB (Buzigi, Pillay, and Siwela 2020a).…”
Section: Pumpkin Powder and Provitamin A Carotenoid Retentionmentioning
confidence: 67%
See 1 more Smart Citation
“…The lactating mothers' suggestion is plausible because 6‐ to 23‐month‐old children in low‐income countries such as Uganda are at a higher risk of developing ID and VAD since they are predominantly fed CFs that are low in iron and vitamin A (Amaral et al., 2018 ; Ekesa et al., 2019 ; Uganda Bureau of Statistics & Inner City Fund, 2018 ). Moreover, developing and testing child acceptability of PVA carotenoid–iron‐rich CFs and testing its acceptability among children in the age range of complementary feeding is feasible (Buzigi et al., 2020b ).…”
Section: Discussionmentioning
confidence: 99%